Condensation sequence of circumstellar cluster seeds (CSCCS) - Gobrecht, David (Frontiers in Astronomy and Space Sciences, 2025)
IntroductionTraditionally, the condensation sequence of circumstellar dust is predicted based on the thermodynamic stabilities of specific condensates in the macroscopic bulk phase. However, at the (sub-) nanometer scale clusters with non-crystalline structures and significantly different properties are energetically favoured.MethodsFor this reason, we study the thermodynamic stabilities of metal oxide clusters with generic stoichiometries of M2O3 and M3O4, where M represents a metal atom. With an upper size limit of 50 atoms, we consider clusters with sizes n = 1–10 for (M2O3)n, and n = 1–7 for (M3O4)n. The M2O3 clusters comprise alumina (Al2O3), Mg-rich pyroxene (MgSiO3) and a size-limited sample of titanates (CaTiO3), whereas the M3O4 clusters include spinel (MgAl2O4), Mg-rich olivine (Mg2SiO4) and calcium aluminates (CaAl2O4).ResultsWe find that, apart from the alumina monomer, the aluminum-bearing clusters (Al2O3)n, n = 1–10, and (MgAl2O4)n, n = 1–7, are favoured over their silicate counterparts (MgSiO3)n, n = 1–10 and (Mg2SiO4)n, n = 1–7. Also, we find that calcium aluminate clusters, CaAl2O4, are energetically more favourable than magnesium aluminate clusters, MgAl2O4. Furthermore, for a limited data set of (CaTiO3)n, n = 1–2, clusters we find significantly larger stabilities than for the other considered (M2O3)n clusters, namely Al2O3 and MgSiO3.DiscussionFuture investigations, in particular on titanates and on Ca-rich silicates, are required to draw a more thorough and complete picture of the condensation sequence at the (sub-)nanoscale.